Staff Management Based On Performance: Application Of A Work Measurement Model In Hospital - Mehdi Yousefi; Maryam Ahmadi; Somayeh Fazaeli (Tehran University of Medical Sciences, 2014)
Background and Aim: Managers are always looking for better ways to improve productivity of staff. The aim of this study was to introduce a model based on work and time measurement for Staff Management based on performance in hospital. Materials and Methods: This descriptive - practical study was conducted in ten steps for a medical documents expert's in a general hospital. The main activities of employees were determined via interview and direct observation. Then expected time, tolerances, final coefficient and work units for each activity were calculated. Finally, the total working units were calculated.  Results: Implementation of introduced model for a medical documents expert's in a general hospital showed that the total work units which the staff was obliged to do in one month was 918 units and the remaining (1160-918) was the extra units. Conclusion: Using appropriate models for the performance management of hospital staff workloads, can help to improve the hospital productivity and staff satisfaction.